A parallel protein surface reconstruction system. (18th July 2008) - Merelli, Ivan; Orro, Alessandro; D'Agostino, Daniele; Clematis, Andrea; , Luciano Milanesi
In this paper we propose a parallel system for protein surface reconstruction based on techniques of computational geometry. The advantage of our modelling system is the production of both superficial and volumetric description of proteins. This is very important in protein analysis from the functional point of view, because many binding sites are buried inside the macromolecule. However the amount of data to process, both in the volume modelling and in extraction phase, may be huge, in proportion to the selected resolution of the output. For this reason the parallel implementation of the system represents a fundamental aspect in reducing the processing time.